Основні проблеми адаптації промисловості м. Києва до умов світової організації торгівлі (СОТ) - Покрещук, О.О.; Онищенко, В.П. (Видавничий дім "Академперіодика" НАН України, 2005)
Розглянуті основні результати науково-дослідницької роботи з питань адаптації промисловості м. Києва до умов СОТ. Показано, що основним напрямом такої підготовки є підвищення конкурентноздатності вітчизняних товаровиробників. Обґрунтовані рекомендації щодо підтримки високотехнологічної та інноваційної сфер промислового комплексу м. Києва та визначені необхідні інституціональні зміни у підприємницькому середовищі в контексті вимог СОТ. В статье рассмотрены основные результаты научно-исследовательской работы по вопросам адаптации промышленности г. Киева к условиям ВТО. Показано, что основным направлением такой подготовки есть повышение конкурентоспособности отечественных товаропроизводителей. Обоснованы рекомендации относительно поддержки высокотехнологической и инновационной сфер промышленного комплекса г. Киева и определены необходимые институциональные изменения в предпринимательской среде в контексте требований ВТО. This article is the basic results of research work above a theme "Scientific – methodical maintenance of preparation Kiev economy to functioning in conditions of finding by Ukraine membership in the World trading organization" are considered. It is shown, that the basic direction of such preparation is strengthenings competitiveness of domestic commodity producers. Recommendations concerning support of highly technological and innovational sphere of an industrial complex of Kiev are proved, determined necessary institutional changes in the enterprise environment in a context of requirements WТО.